Silica-ZnCl2: An Efficient Catalyst for the Synthesis of 4-Methylcoumarins. (16th December 2013) - Datta, Bandita; Pasha, Mohamed Afzal
Abstract : Silica-ZnCl2 has been found to be an efficient and eco-friendly catalyst for the synthesis of substituted 4-methylcoumarins from ethyl acetoacetate and substituted phenols under "neat" conditions in an oil bath at 80°C. The experimental procedure is simple, includes shorter reaction times (15–65 min), compatible with sensitive functional groups, and results in excellent yield of the products.